Pharmacognostic Investigation and Antioxidant Activity of Sphagneticola trilobata - Singhal, Kartik; Majee, Chandana; Sharma, Vikas (Asian Journal of Chemistry, 2021)
Sphagneticola trilobata (L.) or Pruski is a medicinal plant and recognized for the treatment of a variety of ailments and partially explored for their pharmacological activity. The main objective of this present study is to find out the pharmacognosy and antioxidant activity of parts of plant S. trilobata viz. leaves, stem and aerial part. Pharmacognostic investigations for morphological characteristics, determination of plant content, ash values, extractive values, total tannin, flavonoid, alkaloid and phenol contents and preliminary phytochemical study. Antioxidant activity of the leaves, stem and aerial part of the plant and isolated products of S. trilobata, through different methods also included in present work. The morphology of this plant revealed that the leaves are green in colour with white coarse hairs and stem are rounded, green or reddish and maybe coarsely hairy. The antioxidant activity of the methanolic extracts of leaves stem and aerial part of the plant also revealed that the leaves containing higher antioxidant potential compared to other parts. The result of this study could be useful in the identification and preparation of monographs of the plant and also useful in findings the antioxidant potentiality of the plant S. trilobata.